Análise da biodegradação de lixiviado de resíduos sólidos em solo de camada de cobertura de aterro sanitário - NISHIWAKI, Adriana Aparecida Megumi (2016)
By having a high power of contamination to edaphic and hydric resources, the solid waste leachate should be treated properly. Some landfills use the recirculation technique, applying the effluent on the landfill cells, obtaining various benefits such as increasing the internal moisture of the cell that contributes to the breakdown of ungrounded waste, reducing the volume of leachate to be treated and operating costs, soil enrichment mainly of organic matter and nutrients, important for growing vegetation on the slopes, among others. However, it contains heavy metals and high levels of organic matter, can become an environmental liability n the site applied. Thus, this study aimed to evaluate the aerobic biodegradation of leachate in the landfill soil of the Metropolitan Region of Recife and the effects of its application in soil. A soil initial characterization collected in the landfill and raw leachate was made. For leachate biodegradation analysis, it adopted the Bartha´s respirometric method, which consisted of an experiment with five repetitions of four treatments. The treatments were based on soil field capacity (FC), with the percentage of 60%, 65% and 70% humidity range for operation of respirometers proposed by NBR ABNT regulating the methodology. After respirometry, soil samples were characterized. For the determination of surface application rates leachate in an experiment in a greenhouse to evaluate the evaporative loss of leachate according to the application time, for each of the rates used. The amount of leachate added had the same ratio used in the treatments employed in respirometry. The studied soil presented a sandy clay loam texture, low in organic matter and 1.73 x 1012 CFU of bacteria.g-1 of soil and 8.26 x 105 CFU of fungi.mL-1. The leachate used show relation COD/BOD of 0.88 mg.L-1 indicate high biodegradability. The accumulated amounts of CO2 were obtained until the fifteenth day of incubation, 11.38 mg of CO2, 59.94 mg of CO2, 66.35 mg of CO2 and 76.55 mg of CO2 to control treatments 60 FC% 65% FC 70% FC, respectively. All treatments showed greater than 70% biodegradation efficiency, percentage acceptable for use in the treatment of waste soil. The final characterization of the soil after respirometry, there was a significant increase potassium, phosphorus and organic matter in all treatments. Although the application of the leachate, which had 1.2 x 1013 CFU of bacteria.mL-1, 60% FC treatment reduced bacterial CFU to 5.3 x 1011, while the 65% FC treatment remained in the same order (1012), which could be indicative that the leachate reduces the diversity of the most sensitive species in the soil. Treatment 70% of the CC, which obtained the highest number was around 1013. 70% FC treatment, which obtained the highest number was around 1013. The fungi behaved differently from bacteria, with an increase in 60% FC treatment 1.6 x 106, and reduced in the other two treatments. From the qualitative and quantitative results of this work can be concluded the possibility of using the application of landfill leachate in cover layer with clay-sandy soil in regions with a tropical climate, with biodegradation rate above 70% and rate application to 130,43 m3.ha-1. The application of leachate in the soil is a viable alternative treatment of the leachate and reducing its volume up must still observe the proper management of the application of leachate in landfill soil to avoid structural problems in slopes or steep erosion in the form of application of leachate in soil.